Household lifestyle: quartercut / Yufarisha Nur Rania Mohd Yuzakri … [et al.] - Mohd Yuzakri, Yufarisha Nur Rania; Zaharin, Dayang Zahirah; Wan Azhab, Wan Arisa Sofea; Mohamad Azhar, Nor Alysa Atiqa; Roslan, Nur Meelna Marlinie; Izat Amer, Izzat Aiman; Daud, Shahreena (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Quatercut is a cutting board experience redefined by an inventive kitchenware solution. With folding versatility and lots of small puncture holes positioned thoughtfully all over the board, Quatercut has a distinctive design that effectively drains water. Because it stops water buildup and bacterial growth, this innovative design not only makes food preparation more convenient but also encourages hygiene. Users may easily go from cutting to cleaning with Quatercut, making for a smooth culinary experience.